Hydrogen adsorption on calcium, potassium, and magnesium-decorations aluminene using density functional theory. (5th May 2021) - Villagracia, Al Rey; Ong, Hui Lin; Bayasen, Dhan Shemaiah; Lin, Hsin; David, Melanie; Arboleda, Nelson
Abstract: A low-cost hydrogen storage with high capacity is still a bottleneck to achieve a hydrogen economy for a sustainable clean fuel cell vehicle. Aluminene has been identified as a potential hydrogen storage material due to its high surface area. In this work, calcium, potassium, and magnesium were introduced at low concentrations as interstitial dopants to planar aluminene to determine its effects on hydrogen adsorption using density functional theory. Results showed that these impurities can easily be chemisorped with absolute binding energies ranging from 0.95 eV to 3.50 eV on the top, bridge, and hollow sites of aluminene in ascending order. This chemisorption is validated by the overlapping of sp orbitals between the dopant atoms and aluminum as shown in the density of states. Electron transfer from the aluminum to the dopant atoms were observed in the charge density difference allowing reactivity of the hydrogen atoms to the dopants. These materials have zero magnetization and remained metallic. Furthermore, hydrogen molecules were physisorped near the dopants with absolute adsorption energies ranging from 23 meV to 81 meV which would be suitable as a storage material near room temperature. Finally, the calculated gravimetric densities show that aluminene with impurities at low concentrations can still be potential hydrogen storage materials. Graphical abstract: Image 1 Highlights: Mg, Ca and K have successfully ionically bonded with single layer aluminene. Electronic structure was unaltered upon binding of Mg, Ca or K on aluminene. Van der Waals bonding of H2 on Mg, Ca and K decorated aluminene was observed. Calculated gravimetric density for H2 on aluminene with impurities passed the target.